The Armenian Genocide in Letters to the Editor of The Irish Times - Isabella Martini (Studi Irlandesi)
Selected by newspaper editors to keep specific topics current in the news, Letters to the Editor (LTE) have long intertwined with historical events, among which the twentieth century Armenian genocide. At that time international humanitarian workers and political personalities made appeals to the reading public and expressed their indignation for the violence perpetrated to Armenian civilians. Rarely, however, have LTE been studied for their linguistic features. Since they were to meet the ideological agenda of the newspaper’s readers of the time, which recurrent linguistic strategies were used to achieve this? This contribution is part of a more extensive research combining corpus linguistics and discourse analysis to study the representation of the Armenian genocide in historical news discourse.